Pengembangan LKPD dengan Pendekatan STEAM melalui Model PjBL untuk Menumbuhkan Keterampilan Berpikir Kreatif pada Materi Lingkaran Kelas VIII - Wening, Tyas Candra; Hayuhantika, Diesty (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
Creative thinking is an important skill that includes aspects of flexibility, fluency, originality and elaboration. One of the problems encountered in the field is the low creative thinking skills of students. One of the teaching materials that can help teachers overcome this problem is the innovative Student Worksheet (LKPD) with a STEAM approach through the PjBL model in circle material which has relevance to creative thinking skills. This research aims to describe the process and results of developing LKPD using the STEAM approach through the PjBL model to foster creative thinking skills in valid class VIII circle material. This research uses a research and development (R&D) approach referring to the Holistic 4D development model which is adapted to only include the define, design and develop stages. The research results show that the feasibility percentage based on the media expert's assessment is 80% and the feasibility percentage based on the material expert's assessment is 86.8%. Meanwhile, the eligibility percentage based on the results of the practitioner questionnaire was 86.7% and the eligibility percentage obtained based on the results of the user questionnaire was 86.9%. Thus, the product developed is suitable for use as teaching material that fosters students' creative thinking skills.